ISO / IEC _ 25010 For Testing Quality Information System Labor Market (SIPTK) - Keith Francis Ratumbuisang; Yosua Fitsgerald Ratumbuisang (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
This study aims to examine the quality of the developed Mianahsa Labor Market Information System. The research method used is descriptive analysis where each test results are described. There are 5 tests carried out using ISO/IEC25010 namely, suitability, performance efficiency, usability, reliability, and portability. Based on the tests that have been carried out, it is obtained Functional Suitability testing of the labor market information system with a percentage of 100% in the accepted category, Performance Efficiency Testing of the labor market information system with a percentage of 99% I n the fast category, Usability testing of the labor market information system with a percentage of 96.70 % in the very feasible category, Reliability Testing of the labor market information system with a presentation of 90% in the category of success, and Portability testing of the labor market information system with a presentation of 100% in the very good category.